2017
DOI: 10.1007/s40471-017-0096-x
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and Health Disparities

Abstract: Purpose of review African Americans disproportionately suffer from leading causes of morbidity and mortality including cardiovascular disease (CVD), cancer, and preterm birth. Disparities can arise from multiple social and environmental exposures, but how the human body responds to these exposures to result in pathophysiologic states is incompletely understood. Recent findings Epigenetic mechanisms, particularly DNA methylation, can be altered in response to exposures such as air pollution, psychosocial stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 63 publications
(63 reference statements)
1
42
0
Order By: Relevance
“…Site-specific histone modifications at H3K27me3 influence the clinical outcome of patients with early-stage NSCLC. Based on published reports ( 34 36 ), the novel cigarette smoking-induced site-specific histone and DNA methylation markers identified in the present study will have a greater translational impact on understanding the pathogenetic process involved in smoking-mediated lung disease, including lung cancer and other cancer types. The result demonstrated a coexistence of the alteration of DNA methylation and H3K27me3 expression levels in patients with NSCLC, which is consistent with the study by Takeshima et al ( 37 ), which is identified specifically in cancer cells and may be used as a target for epigenetic therapy.…”
Section: Discussionmentioning
confidence: 77%
“…Site-specific histone modifications at H3K27me3 influence the clinical outcome of patients with early-stage NSCLC. Based on published reports ( 34 36 ), the novel cigarette smoking-induced site-specific histone and DNA methylation markers identified in the present study will have a greater translational impact on understanding the pathogenetic process involved in smoking-mediated lung disease, including lung cancer and other cancer types. The result demonstrated a coexistence of the alteration of DNA methylation and H3K27me3 expression levels in patients with NSCLC, which is consistent with the study by Takeshima et al ( 37 ), which is identified specifically in cancer cells and may be used as a target for epigenetic therapy.…”
Section: Discussionmentioning
confidence: 77%
“…By educating providers and community members of the benefits of precision medicine in a culturally sensitive way, we hope to enhance trust in the medical system and en-Teaching Pharmacogenomics Concepts -Johnson et al courage future research participation. [26][27][28] We plan to replicate the program at another FQHC site to bolster data collection. Future assessment of the fidelity of our intervention will require evaluation of community member engagement via social network analysis and monitoring referrals via the electronic medical record.…”
Section: Resultsmentioning
confidence: 99%
“…Some of these mutational processes are related to agingassociated phenomena such as declining DNA damage repair 65,66 , somatic mosaicism and the accumulation of mutations over time 59,67,68 . However, other processes related to immune surveillance, evolutionary selection, disease aetiology and epigenetics are also likely involved [69][70][71] . In addition to such biological factors, lifestyle and socioeconomic considerations like diet 72 and microbiome composition 73 can continuously shape tumour evolution from its earlier steps.…”
Section: Discussionmentioning
confidence: 99%